Growing pains: Pre‐entry experience and the challenge of transition to incumbency - Chen, Pao‐Lien; Williams, Charles; Agarwal, Rajshree (Strategic Management Journal, 2012)
Abstract We examine how entrepreneurial entry by diversifying and de novo firms in new industries leads to different levels of performance. We propose that these types of firms differ in dynamic capabilities, which help them overcome growth impediments and transition to incumbency in the industry. Growth impediments arise at larger size, older tenure levels in industry, and after technological discontinuities. Because of their prior experience, diversifying firms are better equipped to handle the challenges of impediments to growth. Meanwhile, de novo firms, ostensibly tailor‐made for the targeted industry, are more likely to stumble over these growth challenges, and eventually lag behind diversifying firms. We find support for our hypotheses using a near census of firms in the U.S. wireless telecommunications industry over the 1983–2004 period. Copyright © 2011 John Wiley & Sons, Ltd.